2004
DOI: 10.1073/pnas.0400214101
|View full text |Cite
|
Sign up to set email alerts
|

Inducible costimulator-dependent IL-10 production by regulatory T cells specific for self-antigen

Abstract: In this study, we investigated the relationship between the expression levels of self-antigen and the function of self-reactive T cells in the periphery. To this end, we used two rat insulin promoter-ovalbumin (RIP-OVA) transgenic mice (RIP-OVA high , RIP-OVA low ) in which was produced only in pancreatic ␤-islet cells. The OVA-producing transgenic mice were crossed to DO.11.10 (DO) mice expressing a T cell antigen receptor specific for OVA 323

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 44 publications
3
47
0
1
Order By: Relevance
“…This suggested that HCV-specific T-cells are maintained at similar frequency, scope and antigenic hierarchy in chronic HCV infection as those in recovered HCV infection but are polarized toward IL-10 production rather than the IFNγ production characteristic of spontaneous HCV clearance. Possible explanations for this finding include altered T-cell maturation due to virus-induced dysfunction of antigen-presenting cells (29,50,51), viral epitope mutation (52), or altered T-cells costimulation (53)(54)(55). In the chronic phase, peripheral HCV-specific Tr1 response did not correlate with CD4 + CD25 + regulatory T-cell frequency, distinguishing Tr1 cells from CD4 + CD25 + Tregs (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that HCV-specific T-cells are maintained at similar frequency, scope and antigenic hierarchy in chronic HCV infection as those in recovered HCV infection but are polarized toward IL-10 production rather than the IFNγ production characteristic of spontaneous HCV clearance. Possible explanations for this finding include altered T-cell maturation due to virus-induced dysfunction of antigen-presenting cells (29,50,51), viral epitope mutation (52), or altered T-cells costimulation (53)(54)(55). In the chronic phase, peripheral HCV-specific Tr1 response did not correlate with CD4 + CD25 + regulatory T-cell frequency, distinguishing Tr1 cells from CD4 + CD25 + Tregs (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports indicating a role for ICOS in the induction and function of regulatory T cells (Tregs) (12)(13)(14)(15)(16)(17). In distinct mouse models such as experimental allergic encephalomyelitis (EAE) and autoimmune type 1 diabetes, blockade of ICOS signaling by anti-ICOS Abs interrupted the balance between regulatory and effector T cells and worsened disease, indicating a role for ICOS in promoting tolerance and restraining autoimmunity (12,18).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…Although MR1-restricted V␣19i T cells express low levels of CD25, they do not express FoxP3 as determined by RT-PCR of RNA from sorted cells (data not shown). ICOS is associated with IL-10 production (23) and may reflect encounter with self ligand; for instance, ICOS is expressed on naive DO11.1 transgenic T cells specific for OVA 323-339 from mice expressing high levels of OVA under control of the rat insulin promoter (24). Overall, these data are consistent with the observation that human MAIT cells have an activated/memory phenotype (2) and, furthermore, demonstrate that a T cell population phenotypically similar to V␣14i NK T cells develops in V␣19i transgenic mice on an MR1 ϩ/ϩ (but not MR1 Ϫ/Ϫ ) background and that 25-50% of this population expresses NK1.1.…”
Section: Nk11mentioning
confidence: 99%